On the feasibility of multiple assessment of dose using CW-OSL technique in Al2O3:C. (November 2015) - Rawat, N.S.; Muthe, K.P.; Dhabekar, Bhushan; Gaikwad, N.P.; Kulkarni, M.S.
Abstract: The culmination of Continuous Wave OSL (CW-OSL) acquisition after initial few seconds offers improvement in dose detection threshold for Al2 O3 :C. Consequently, the traps from which dose information can be retrieved are still occupied by charge carriers and therefore can be stimulated multiple number of times for extracting OSL signal. This offers an approach for reassessment of the dose in an inadvertent circumstance of dose information being lost. Calibration tables and curves are generated for different stimulation intensities (ranging from 32 to 72 mW/cm 2 ) and signal integration times (ranging from 1 to 10 s) that can be used for re-estimation of the doses lying in the range of 1 mGy to 1 Gy. The qualitative as well as quantitative analysis of the observed trends with respect to stimulation intensity and signal integration time is carried out. The behaviour of dose response curves for successive readout numbers is also studied. Highlights: An approach based on CW-OSL technique is suggested for dose re-estimation in Al2 O3 :C. Calibration tables and curves are generated for different stimulation intensities and signal integration times. The behaviour of dose response curves for a successive readout numbers is found to be dose independent. Implications of these results with context to research and routine applications are discussed.